2017
DOI: 10.1111/njb.01623
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of pollen in indoor air samples as revealed by DNA metabarcoding

Abstract: We conducted DNA metabarcoding (based on the nuclear ITS2 region) to characterize indoor pollen samples (possibly accompanied by other plant fragments) and to discover whether there are seasonal changes in their taxonomic diversity. It was shown that DNA metabarcoding has potential to allow a good discovery of taxonomic diversity. The number of spermatophyte families and genera varied greatly among sampling sites (pooled results per building) and times, between 9–40 and 10–66, respectively. Comparable Shannon'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Typically, airborne eDNA research has mainly discussed findings in relation to human allergens and other aspects of human health Craine et al, 2016;Folloni et al, 2012;Korpelainen & Pietilainen, 2017;Kraaijeveld et al, 2015). Building upon these studies, Johnson, Cox, and Barnes () found that airborne eDNA could detect both wind-pollinated Bouteloua genus and insect pollinated honey mesquite (Prosopis glandulosa Torr.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, airborne eDNA research has mainly discussed findings in relation to human allergens and other aspects of human health Craine et al, 2016;Folloni et al, 2012;Korpelainen & Pietilainen, 2017;Kraaijeveld et al, 2015). Building upon these studies, Johnson, Cox, and Barnes () found that airborne eDNA could detect both wind-pollinated Bouteloua genus and insect pollinated honey mesquite (Prosopis glandulosa Torr.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Nuñez et al [17] utilized next-generation sequencing to confirm it was possible to genetically identify bacterial, fungi, and pollen samples captured from a Hirst-type spore trap with the goal of understanding more about urban allergens and health hazards in the air. Lastly, in addition to outdoor samples, Korpelainen and Pietilainen [18] successfully characterized indoor pollen samples with a metabarcoding approach to understand the effects of pollen and indoor airborne particles on humans. While this brief review of airborne genetic sampling shows how various methods and questions can be addressed within these studies, it also highlights how these studies focus primarily on pollen detection.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, statistical models can be built for total variation detection at a specific locus [114]. This has already been done for taxon biodiversity [114,175,176]. Additionally, estimates of relatedness between populations could be based on genetic similarities [42,68,69].…”
Section: Further Developments and Future Technologiesmentioning
confidence: 99%